Application analyze of a ground source heat pump system in a nearly zero energy building in China. (15th April 2017) - Li, Huai; Xu, Wei; Yu, Zhen; Wu, Jianlin; Sun, Zhifeng
Abstract: Ground source heat pump system has been widely utilized in office buildings in China. Its application in nearly zero energy office building pioneers an innovation in China. This paper focuses on real operation introduction and performance analysis of a Ground Source Heat Pump (GSHP) system in a nearly zero energy building (NZEB) with different HVAC terminal for the first time. The paper introduces the nearly zero energy building with a general presentation of its energy system, then analyzes GSHP system operation and soil temperature variation from November 2014 to September 2015 based on real operation data. The analyses manifests that the HP2# worked under an average COP of about 5.4 and 5.0 in summer and winter, respectively and HP1# worked under an average COP of 3.9 and 3.0 in winter and summer respectively. In the winter season floor and ceiling radiation system has a relatively higher performance than radiator system due to low supply water temperature going into the room. Room temperature keeps above 20 °C in the winter season and fluctuated around 26 °C in the summer season. Good room temperature and COP proves the GSHP system functions excellently. Soil temperature could recover in one year operation. Highlights: Evaluated application of a GSHP system in a nearly zero energy building with more than one year precisely monitoring data. Heat Pump operation with different HVAC terminals is analyzed. Operating characteristics of GSHP operation in nearly zero energy building is discussed. Indoor environment in heating and cooling season as well as soil temperature in different position and depth are discussed. Provide some good suggestions on combination of GSHP with nearly zero energy building and its operation.